2013
DOI: 10.1002/glia.22576
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone treatment results in enhanced release of peptidergic vesicles in astrocytes via cytoskeletal rearrangements

Abstract: While the effect of stress on neuronal physiology is widely studied, its effect on the functionality of astrocytes is not well understood. We studied the effect of high doses of stress hormone corticosterone, on two physiological properties of astrocytes, i.e., gliotransmission and interastrocytic calcium waves. To study the release of peptidergic vesicles from astrocytes, hippocampal astrocyte cultures were transfected with a plasmid to express pro-atrial natriuretic peptide (ANP) fused with the emerald green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…Our observations agree well with the very few reports of the effect of corticosterone or stress on the astrocyte cytoskeleton. Chatterjee and Sikdar (2013) showed that incubating cultured rat hippocampus astrocytes for 3 h with 100 nM corticosterone caused the actin cytoskeleton to change and lose stress fibers, as in our model. Such actin remodeling also occurs in other cell types (trabecular meshwork cells, epithelial cells) in response to dexamethasone (Rubenstein et al 2003;Clark et al 2005;Yuan et al 2013).…”
Section: Discussionsupporting
confidence: 64%
“…Our observations agree well with the very few reports of the effect of corticosterone or stress on the astrocyte cytoskeleton. Chatterjee and Sikdar (2013) showed that incubating cultured rat hippocampus astrocytes for 3 h with 100 nM corticosterone caused the actin cytoskeleton to change and lose stress fibers, as in our model. Such actin remodeling also occurs in other cell types (trabecular meshwork cells, epithelial cells) in response to dexamethasone (Rubenstein et al 2003;Clark et al 2005;Yuan et al 2013).…”
Section: Discussionsupporting
confidence: 64%
“…In vitro, glucocorticoid treatment induces rapid increases in astrocyte Ca 2+ signalling suggestive of an activation of non‐genomic pathways downstream of glucocorticoid receptors. Glucocorticoid treatment of astrocytes in culture also enhances neuropeptide (ie, atrial natriuretic peptide) release from astrocytes, promotes glutamate recycling, and leads to increases in GFAP‐immunoreactivity and rearrangement of F‐actin fibres, indicative of cellular stress . By contrast, chronic treatment of primary astrocytes in culture with glucocorticoids reduces cellular proliferation and glucocorticoid receptor expression .…”
Section: Astrocytes and The Neuroendocrine Regulation Of The Stress Rmentioning
confidence: 99%
“…recycling, and leads to increases in GFAP-immunoreactivity and rearrangement of F-actin fibres, indicative of cellular stress. 143,144 By contrast, chronic treatment of primary astrocytes in culture with glucocorticoids reduces cellular proliferation and glucocorticoid receptor expression. 145,146 This is recapitulated in an in vivo rodent model where astrocyte number is reduced in the frontal cortex by chronic HPA axis activation via ACTH administration 145 or in response to chronic corticosterone treatment, with or without additional behavioural stress.…”
Section: A S Tro C Y Te S and The Neuroendo Crine Reg Ul Ati On Of mentioning
confidence: 99%
“…Glucocorticoids appear to synergize with NA in the mobilization of energy during a stress response (Joëls and Baram, 2009 ). Astrocytes express GRs (Bohn et al, 1994 ; Simard et al, 1999 ) and corticotrophin releasing hormone receptors (Kapcala and Dicke, 1992 ), and respond to glucocorticoids with calcium waves (Simard et al, 1999 ) and peptide release (Chatterjee and Sikdar, 2013 ). The breakdown of glycogen following NA stimulation is followed by a seemingly compensatory increase in rates of glycogenesis (Sorg and Magistretti, 1992 ), which is inhibited by dexamethasone (Allaman et al, 2004 ), a synthetic form of glucocorticoid (Sapolsky et al, 2000 ).…”
Section: The Functions Of Lactate In Memory Formation: Stress Neurommentioning
confidence: 99%